Tinjauan Hukum terhadap Perjanjian Kemitraan Inti-Plasma di Perkebunan Kelapa Sawit: Perspektif Prinsip Kemitraan dan Pengawasan - Nisrina Hanun; Elisatris Gultom; Nun Harieti (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
A partnership agreement is a form of business collaboration, either directly or indirectly, that is established based on the principles of mutual need, mutual trust, mutual reinforcement, and mutual benefit. Such partnerships generally involve Micro, Small, and Medium Enterprises (MSMEs) working with larger businesses in order to create a fairer and more sustainable business relationship. However, in practice, the implementation of partnership agreements often does not reflect these fundamental principles. This is also evident in the nucleus-plasma scheme within the palm oil plantation sector, where the relationship between the nucleus companies and plasma farmers tends to show an imbalance of bargaining power. This study aims to examine the application of partnership principles in the implementation of nucleus-plasma agreements in palm oil plantations, viewed from the perspective of prevailing legislation, particularly the Law on Micro, Small, and Medium Enterprises (MSME Law). The findings indicate that the application of partnership principles has not yet been fully implemented consistently. The partnership relationship remains unequal and is largely dominated by the nucleus companies, creating a sense of injustice for plasma farmers. In terms of supervision, the Indonesian Business Competition Supervisory Commission (KPPU) plays a crucial role in ensuring that partnership agreements are carried out in line with these principles. One of the measures taken is monitoring the implementation of behavioral change commitments by business actors. KPPU ensures that nucleus companies do not abuse their dominant position and continue to provide fair opportunities for plasma farmers. Therefore, this study highlights the importance of strengthening oversight and enforcing regulations so that the objectives of nucleus-plasma partnerships in palm oil plantations can truly be realized in accordance with the principles mandated by law.